Antibacterial synergy between linezolid and baicalein against methicillin-resistant Staphylococcus aureus biofilm in vivo. (October 2020) - Liu, Tangjuan; Luo, Jing; Bi, Guan; Du, Zhongye; Kong, Jinliang; Chen, Yiqiang
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) can form biofilms, which prevents the penetration of antibiotics, decreasing their efficacy. This study investigated whether baicalein has synergistic antibacterial effects with linezolid in vivo . We cultivated MRSA 17546 biofilms on silicone implants and inserted them into the air pouches of rat models. The rats were treated with linezolid, baicalein, or a combination therapy for three consecutive days. All treatments reduced the number of colony-forming units (CFU) in the biofilms compared to the control ( p < 0.05). However, by day two, the CFU counts were significantly lower in the combination group than in the individual treatment groups ( p < 0.05). Histological analysis of the air pouches showed that the severity of the inflammatory cell infiltration was severe in the combination therapy group. In the combination group, the biofilm structure on the implant's surface was sparse and more free colonies could be seen by scanning electron microscopy (SEM); by day three, no obvious biofilm was observed. The serum levels of Staphylococcus enterotoxin A (SEA), C-reactive protein (CRP), and procalcitonin (PCT) were the lowest in the group where rats were treated with the combination of baicalein and linezolid ( p < 0.05) compared to other groups. The results suggest that baicalein may inhibit the accessory gene regulator system, reducing the expression of SEA, thus lowering CRP and PCT levels. Furthermore, the inhibitory effect was more pronounced when baicalein was combined with linezolid. These results provide an important basis for the development of a new combination regimen to treat patients with biofilm-associated MRSA infections. Highlights: Linezolid with baicalein's combination was tested against MRSA biofilms.